Specific Capacitance and Cyclic Stability of Graphene Based Metal/Metal Oxide Nanocomposites： A Review - Anwar, Abdul Waheed; Majeed, Abdul; Iqbal, Nadeem; Ullah, Wasi; Shuaib, Ahmad; Ilyas, Usman; Bibi, Fozia; Rafique, Hafiz Muhammad (Journal of materials science & technology, 2015)
Graphene has become a worldwide admired material among researchers and scientists equally due to its unique richness in mechanical strength, electrical conductivity, optical and thermal properties. Re- searchers have explored that the composite materials based on graphene and metal/metal oxide nanostructures possess excellent potential for energy storage technologies. In particular, supercapacitors based on such composite materials have engrossed the extreme interest of researchers for its rapid charging/discharging time, safe operation and longer cyclic constancy. Till now, several fabrication techniques for composite materials and their energy storage applications have been explored. Here, specially, we have concentrated on the hottest research progress for the fabrication of graphene oxide and metal/metal oxide nanocomposites. We also emphasized on the characteristics and properties of supercapacitors fabricated using these composite materials. Moreover, our study is focused on the specific capacitance and cyclic stability of various composites to haul out the most efficient material for supercapacitor applications.